Pharmacokinetics and toxicology studies of new neuronal growth factor - Mir Sadat-Ali, Dakheel A Al-Dakheel, Khulood S. Al Ghamdi, Shahanas Chathoth, Fadel A. Al-Omar, Hassan A. Al Saad, Ayesha Ahmed (Journal of Applied Pharmaceutical Science, 2024)
The objective of this study was to examine the pharmacokinetics and toxicology of major organs after intramuscular injection of new neuronal growth factor (NNGF) in rats and sheep and to gather evidence for future clinical trials so that new treatment modalities of successful treatment can be available for peripheral nerve injuries. For pharmacokinetics, we injected 70 skeletally mature Sprague Dawley rats intramuscularly with 5 mg/kg of body weight of NNGF, and we collected blood samples at 0, 30, 60, 120, 240, 360, and 480 minutes. We quantified the concentration of peptide present in the rat plasma samples collected at multiple time intervals using high-performance liquid chromatography. For toxicology, we included 20 rats, 10 in the control group 10 in the study group, 20 adult sheep, 10 in the control group and 10 in the study group. In the study groups, we injected 100 mg/kg of body weight of the NNGF intramuscularly for 7 days for rats and sheep. We observed all animals clinically daily to assess behavioural and dietary activities. After 2 weeks, we euthanized the animals and observed and weighed each one’s heart, kidney, liver, and brain. We harvested the organs and sent them out for histopathological studies. We found no significant difference in body weight or food residue observed between the control and the study groups. All animals withstood the study well, and no deaths occurred in any group until we finished the experiment. We detected NNGF content in the plasma by liquid chromatography. Immediately after injection, the NNFG level was 0.108 ± 0.034 μM. It rose to 0.166 ± 0.024 μM at 30 minutes and peaked at 60 minutes at 0.362 ± 0.409 μM. At 120 minutes, the level started decreasing (0.202 ± 0.209 μM), and after 240 minutes, it reached 0.086 ± 0.044 μM. At 320 minutes, we detected no NNGF in the plasma and no abnormality in any of the animals’ organs compared to the control group in the sheep or rats. This study showed that with an intramuscular injection of 5 mg/kg of body weight of NNGF, the serum levels peaked at 60 minutes, showing rapid absorption and excretion. Moreover, the histopathology showed no toxic effects on the organs tested.
Keywords: New neuronal growth factor, pharmacokinetics, intramuscular injection, toxicity